2021
DOI: 10.1021/acsami.1c08399
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Growth of AlN Films on Magnetostrictive Foils for High-Magnetoelectric-Response Thin-Film Composites

Abstract: This study reports a strong ME effect in thin-film composites consisting of nickel, iron, or cobalt foils and 550 nm thick AlN films grown by PE-ALD at a (low) temperature of 250 °C and ensuring isotropic and highly conformal coating profiles. The AlN film quality and the interface between the film and the foils are meticulously investigated by means of high-resolution transmission electron microscopy and the adhesion test. An interface (transition) layer of partially amorphous Al x O y /AlO x N y with thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…87,117 Nguyen et al used plasma-enhanced atomic layer deposition (PE-ALD) technology to fabricate an aluminum nitride (AlN)/Ni thin-film composite at a low temperature of 250°C. 89 Due to the high zero-field q of Ni foil (1.4 ppm Oe −1 ), the AlN/Ni composite delivered a high SME coefficient. At a Ni foil thickness of 7.5, 15, and 30 μm, the maximum α SME observed at the offresonance frequency of 46 Hz was 3.3, 2.7, and 3.1 V cm −1 Oe −1 , respectively.…”
Section: Metal Nimentioning
confidence: 99%
See 1 more Smart Citation
“…87,117 Nguyen et al used plasma-enhanced atomic layer deposition (PE-ALD) technology to fabricate an aluminum nitride (AlN)/Ni thin-film composite at a low temperature of 250°C. 89 Due to the high zero-field q of Ni foil (1.4 ppm Oe −1 ), the AlN/Ni composite delivered a high SME coefficient. At a Ni foil thickness of 7.5, 15, and 30 μm, the maximum α SME observed at the offresonance frequency of 46 Hz was 3.3, 2.7, and 3.1 V cm −1 Oe −1 , respectively.…”
Section: Metal Nimentioning
confidence: 99%
“…A Ni/BZT–BCT/Ni SME composite laminated with <011>‐oriented BZT–BCT piezoelectric layer and Ni layer realized a comparable α SME to that of the Ni/(PMN–PZT)/Ni (Ni/single‐crystal Pb(Mg 1/3 Nb 2/3 )O 3 –Pb(Zr,Ti)O 3 /Ni) lead‐based layered composite and was significantly higher than those of Ni/PZT/Ni composites 87,117 . Nguyen et al used plasma‐enhanced atomic layer deposition (PE–ALD) technology to fabricate an aluminum nitride (AlN)/Ni thin‐film composite at a low temperature of 250°C 89 . Due to the high zero‐field q of Ni foil (1.4 ppm Oe −1 ), the AlN/Ni composite delivered a high SME coefficient.…”
Section: Sme Composites and Structuresmentioning
confidence: 99%
“…They found the ME voltage coefficient of 94.5 V/cm·Oe, which is large enough for harvesting electromagnetic energy for suitable applications. Nguyen et al [ 69 ] developed AlN/Ni, AlN/Fe, and AlN/Co thin-film ME composites and studied their energy-harvesting performance.…”
Section: Me Thin Film Energy Harvestersmentioning
confidence: 99%
“…Nickel is also an easy-to-process material for thin-film applications and, compared to magnetostrictive compound materials, relatively simple to describe as a model system. Additionally, if necessary, it provides the possibility to be processed as a single crystalline material, e.g., an inverted stack allows the deposition of AlN on (polycrystalline) Ni foils, which can be replaced with single crystalline ones, with a high interface quality and c-axis orientation of AlN, resulting in a strong magnetoelectric response compared to Fe and Co [17]. Comparably few references can be found that target sensors in the microelectromechanical system (MEMS) regime [18][19][20], a highly interesting transition region where anisotropic material properties show increasing influence on the device characteristics, when the sensor dimensions start to reach the order of magnitude of individual crystals within the (poly-)crystalline material.…”
Section: Introductionmentioning
confidence: 99%